2014
DOI: 10.1088/1674-1056/23/5/057802
|View full text |Cite
|
Sign up to set email alerts
|

Up-conversion luminescence properties and energy transfer of Er 3+ /Yb 3+ co-doped oxyfluoride glass ceramic containing CaF 2 nano-crystals

Abstract: Ma Chen-Shuo(马辰硕) a) , Jiao Qing(焦 清) a) , Li Long-Ji(李龙基) a) , Zhou Da-Cheng(周大成) a) , Yang Zheng-Wen(杨正文) a)b) , Song Zhi-Guo(宋志国) a)b) , and Qiu Jian-Bei(邱建备) a)b) † a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Weakly interacting dopants with rare-earth ions are favourable for the possibility of production of the compact laser. [10][11][12][13] In particular, the case of Er 3+ is of considerable interest, [14][15][16][17][18][19][20][21] since it has been found that the visible and infrared photoluminescence spectra of Er 3+ ions with low concentration in MF 2 -type fluorides are closely related to the different charge compensation centers, mainly resulting from the modification of local site symmetry and local lattice distortion.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Weakly interacting dopants with rare-earth ions are favourable for the possibility of production of the compact laser. [10][11][12][13] In particular, the case of Er 3+ is of considerable interest, [14][15][16][17][18][19][20][21] since it has been found that the visible and infrared photoluminescence spectra of Er 3+ ions with low concentration in MF 2 -type fluorides are closely related to the different charge compensation centers, mainly resulting from the modification of local site symmetry and local lattice distortion.…”
Section: Introductionmentioning
confidence: 99%